Influence of self‐esteem on health‐related quality of life in children and adolescents with autism spectrum disorders - Minobu Ikehara; Natsuko Kashida; Rio Ishida; Ryo Mizui; Manabu Makinodan; Kazuhiko Yamamuro (PCN Reports)
Abstract Aim Autism spectrum disorder (ASD) is a neurodevelopmental condition that markedly impairs the physical, emotional, and social domains of health‐related quality of life (HRQOL). Children with ASD typically report lower HRQOL than their neurotypical peers. This study investigated the impact of self‐esteem and depressive symptoms on HRQOL in children with ASD and explored the discrepancies between parent‐reported and self‐reported HRQOL. Methods This study involved 94 participants, comprising 50 children with ASD and 44 typically developed. HRQOL was measured using the J‐KIDSCREEN‐52 (self‐reported and parent‐reported). Self‐esteem, depressive symptoms, and social support were assessed using the Rosenberg Self‐Esteem Scale, the Depression Self‐Rating Scale for Children, and the Multidimensional Scale of Perceived Social Support, respectively. Discrepancies between parent‐reported and self‐reported HRQOL were examined. Multiple regression analyses were performed to determine the influence of depressive symptoms and self‐esteem on HRQOL. Results Children with ASD showed markedly lower HRQOL than their neurotypical peers. Discrepancies between parent‐reported and self‐reported HRQOL revealed differing perspectives. Higher depressive symptoms were strongly correlated with poorer HRQOL. Conversely, higher self‐esteem was linked to better HRQOL, notably in terms of self‐perception. Social support also markedly influenced HRQOL. Conclusion This study underscores the necessity of addressing depressive symptoms, self‐esteem, and social support as interventions to enhance HRQOL in children with ASD. The differences between parent‐reported and self‐reported HRQOL highlight the need to incorporate both views into clinical assessments for comprehensive and effective interventions. Future research should explore these dynamics longitudinally and across diverse populations to refine the intervention strategies.